(untitled) (Research, Society and Development, 2023)
Progressive Hemorrhagic Myelomalacia (HpM) is a disease caused by a spinal cord injury that leads to necrosis of the affected spinal cord area, it can occur in focal form or ascending and descending way. After the injury, neurological clinical signs are observed in the animals and the progression of the disease is rapid. All dog breeds can have MHP, currently, shih-tzu and French bulldog are the most prevalent. For the diagnosis, a clinical and neurological evaluation is necessary, in addition to specific complementary exams such as magnetic resonance imaging. There is still no clinical treatment protocol for the disease, and one of the alternatives is surgical treatment or euthanasia, when there is a severity in the clinical signs, the prognosis of MHP, in general, is unfavorable. The objective of this study was to report the case of a Shih-tzu dog that after surgical referral for hemilaminectomy, presented diffuse alteration in the medulla and was diagnosed with myelomalacia through durotomy. Soon after the surgical procedure, the animal presented a stable clinical picture, normodipsia and normofagia, but presented irreversible paraplegia.